Chemodiversity and biological activity of essential oils from three species from the Euphorbia genus. (28th September 2020) - Sinan, Kouadio Ibrahime; Etienne, Ouattara Katinan; Stefanucci, Azzurra; Mollica, Adriano; Mahomoodally, Mohamad Fawzi; Jugreet, Sharmeen; Rocchetti, Gabriele; Lucini, Luigi; Aktumsek, Abdurrahman; Montesano, Domenico; Ak, Gunes; Zengin, Gokhan
Abstract: Several studies demonstrated the wide pharmacological properties of extracts and essential oils (EOs) prepared from Euphorbia species. In the present study, the chemical composition and biological activities of EOs from three different Euphorbia species were evaluated using in vitro methods. A total of 29, 33 and 42 constituents were identified in the EOs of E hirta, E convolvuloides and E heterophylla, respectively. The EOs exhibited in vitro radical scavenging potential in the ABTS assay (2.89‐21.50 mg/g). Additionally, an inhibitory effect on acetylcholinesterase (4.23‐5.12 mg/g) was detected. Besides, remarkable tyrosinase inhibition was reported by the EOs (95.24‐113.74 mg/g). Molecular docking was also performed to elucidate the binding interactions between selected EO components and enzymes. Phytol and geranyl‐(E)‐acetone had a good binding with tyrosinase in the molecular docking. This study highlighted the promising pharmacological profiles of these EOs as natural sources of antioxidants as well as cholinesterase and tyrosinase inhibitors that could be further explored in the management of human ailments in food and pharmaceutical industries. Abstract : Our findings could be provided new raw materials for food and pharmaceutical industries.